Religious linguistic identity and national values in early education - Arini, Mike Marta (Journal of Religion and Linguistics, 2025)
Indonesia’s pluralism is both a national strength and a source of potential intergroup tension; much of the documented intergroup antagonism among adults (ethnic, religious, and intra-religious) traces back to socialization processes that begin in childhood. This qualitative case study examines how national identity is cultivated in two primary schools in Semarang (one public, one private Islamic) through observation, interviews, and document analysis. Using thematic coding, the study finds that schools deploy an integrated triadic strategy—cognitive, affective, and behavioral—to teach national belonging. Although multiple identities (ethnic, environmental) are fostered, national and religious identities are intentionally foregrounded and strategically linked so they appear complementary rather than competitive. While many school practices successfully promote inclusive identification, outcomes are uneven, highlighting the need for longitudinal research on the durability of school-based identity formation across families and communities.